Rethinking Fuelwood: People, Policy and the Anatomy of a Charcoal Supply Chain in a Decentralizing Peru - Bennett, A.; Cronkleton, P.; Menton, M.; Malhi, Y. (MDPI, 2018)
In Peru, as in many developing countries, charcoal is an important source of fuel. We examine the commercial charcoal commodity chain from its production in Ucayali, in the Peruvian Amazon, to its sale in the national market. Using a mixed-methods approach, we look at the actors involved in the commodity chain and their relationships, including the distribution of benefits along the chain. We outline the obstacles and opportunities for a more equitable charcoal supply chain within a multi-level governance context. The results show that charcoal provides an important livelihood for most of the actors along the supply chain, including rural poor and women. We find that the decentralisation process in Peru has implications for the formalisation of charcoal supply chains, a traditionally informal, particularly related to multi-level institutional obstacles to equitable commerce. This results in inequity in the supply chain, which persecutes the poorest participants and supports the most powerful actors.